Flexible energy harvester from an organic ferroelectric ammonium salt - Gupta, Rishabh; Sahoo, Supriya; Deswal, Swati; Kothavade, Premkumar; Dixit, Prashant; Zareba, Jan K.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Chemistry-An Asian Journal, 2021)
Organic ferroelectrics due to their low cost, easy preparation, light weight, high flexibility and phase stability are gaining tremendous attention in the field of portable electronics. In this work, we report the synthesis, structure and ferroelectric behavior of a two-component ammonium salt 2, containing a bulky [Bn(4-BrBn)NMe2](+) (Bn=benzyl and 4-BrBn=4-bromobenzyl) cation and tetrahedral (BF4)(-) anion. The structural analysis revealed the presence of rich non-classical C-H...F and C-H...Br interactions in this molecule that were quantified by Hirshfeld surface analysis. The polarization (P) vs. electric field (E) hysteresis loop measurements on 2 gave a remnant polarization (P-r) of 14.4 mu C cm(-2) at room temperature. Flexible polymer composites with various (5, 10, 15 and 20) weight percentages (wt%) of 2 in thermoplastic polyurethane (TPU) were prepared and tested for mechanical energy harvesting applications. A notable peak-to-peak output voltage of 20 V, maximum current density of 1.1 mu A cm(-2) and power density of 21.1 mu W cm(-2) were recorded for the 15 wt% 2-TPU composite device. Furthermore, the voltage output generated from this device was utilized to rapidly charge a 100 mu F capacitor, with stored energies and measured charges of 156 mu J and 121.6 mu C, respectively.
Keywords: Dielectric; energy harvesting; ferroelectricity; organic composites; piezoelectric

3D-printed polymer composite devices based on a ferroelectric chiral ammonium salt for high-performance piezoelectric energy harvesting - Sahoo, Supriya; Kothavade, Premkumar Anil; Naphade, Dipti R.; Torris, Arun; Praveenkumar, Balu; Zareba, Jan K.; Anthopoulos, Thomas D.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Materials Horizons, 2023)
Three-dimensional printing (3DP) is an emerging technology to fabricate complex architectures, necessary to realize state-of-the-art flexible and wearable electronic devices. In this regard, top-performing devices containing organic ferro- and piezoelectric compounds are desired to circumvent significant shortcomings of conventional piezoceramics, e.g. toxicity and high-temperature device processibility. Herein, we report on a 3D-printed composite of a chiral ferroelectric organic salt {[Me3CCH(Me)NH3][BF4]} (1) with a biodegradable polycaprolactone (PCL) polymer that serves as a highly efficient piezoelectric nanogenerator (PENG). The ferroelectric property of 1 originates from its polar tetragonal space group P4(2), verified by P-E loop measurements. The ferroelectric domain characteristics of 1 were further probed by piezoresponse force microscopy (PFM), which gave characteristic `butterfly' and hysteresis loops. The PFM amplitude vs. drive voltage measurements gave a relatively high magnitude of the converse piezoelectric coefficient for 1. PCL polymer composites with various weight percentages (wt%) of 1 were prepared and subjected to piezoelectric energy harvesting tests, which gave a maximum open-circuit voltage of 36.2 V and a power density of 48.1 mu W cm(-2) for the 10 wt% 1-PCL champion device. Furthermore, a gyroid-shaped 3D-printed 10 wt% 1-PCL composite was fabricated to test its practical utility, which gave an excellent output voltage of 41 V and a power density of 56.8 mu W cm(-2). These studies promise the potential of simple organic compounds for building PENG devices using advanced manufacturing technologies.

Ferroelectric aminophosphonium cyanoferrate with a large electrostrictive coefficient as a piezoelectric nanogenerator - Vijayakanth, Thangavel; Sahoo, Supriya; Kothavade, Premkumar; Sharma, Vijay Bhan; Kabra, Dinesh; Zareba, Jan K. K.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2023)
Hybrid materials possessing piezo- and ferroelectric properties emerge as excellent alternatives to conventional piezoceramics due to their merits of facile synthesis, lightweight nature, ease of fabrication and mechanical flexibility. Inspired by the structural stability of aminophosphonium compounds, here we report the first A(3)BX(6) type cyanometallate [Ph-2((PrNH)-Pr-i)(2)P](3)[Fe(CN)(6)] (1), which shows a ferroelectric saturation polarization (P-s) of 3.71 mu C cm(-2). Compound 1 exhibits a high electrostrictive coefficient (Q(33)) of 0.73 m(4) C-2, far exceeding those of piezoceramics (0.034-0.096 m(4) C-2). Piezoresponse force microscopy (PFM) analysis demonstrates the polarization switching and domain structure of 1 further confirming its ferroelectric nature. Furthermore, thermoplastic polyurethane (TPU) polymer composite films of 1 were prepared and employed as piezoelectric nanogenerators. Notably, the 15 wt % 1-TPU device gave a maximum output voltage of 13.57 V and a power density of 6.03 mu W cm(-2).
Keywords: Cyanometallates; energy conversion; H-bonding; hybrid composites; Phosphorus

Highly electrostrictive salt cocrystal and the piezoelectric nanogenerator application of its 3D-printed polymer composite - Sahoo, Supriya; Panday, Rishukumar; Kothavade, Premkumar; Sharma, Vijay Bhan; Sowmiyanarayanan, Anirudh; Praveenkumar, Balu; Zareba, Jan K.; Kabra, Dinesh; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (ACS Applied Materials and Interfaces, 2024)
Ionic cocrystals with hydrogen bonding can form exciting materials with enhanced optical and electronic properties. We present a highly moisture-stable ammonium salt cocrystal [CH3C6H4CH(CH3)NH2][CH3C6H4CH(CH3)NH3][PF6] ((p-TEA)(p-TEAH)PF6) crystallizing in the polar monoclinic C2 space group. The asymmetry in (p-TEA)(p-TEAH)PF6 was induced by its chiral substituents, while the polar order and structural stability were achieved by using the octahedral PF6- anion and the consequent formation of salt cocrystal. The ferroelectric properties of (p-TEA)(p-TEAH)PF6 were confirmed through P-E loop measurements. Piezoresponse force microscopy (PFM) enabled the visualization of its domain structure with characteristic ``butterfly'' and hysteresis loops associated with ferro- and piezoelectric properties. Notably, (p-TEA)(p-TEAH)PF6 exhibits a large electrostrictive coefficient (Q(33)) value of 2.02 m(4) C-2, higher than those found for ceramic-based materials and comparable to that of polyvinylidene difluoride. Furthermore, the composite films of (p-TEA)(p-TEAH)PF6 with polycaprolactone (PCL) polymer and its gyroid-shaped 3D-printed composite scaled-up device, 3DP-Gy, were prepared and evaluated for piezoelectric energy-harvesting functionality. A high output voltage of 22.8 V and a power density of 118.5 mu W cm(-3) have been recorded for the 3DP-Gy device. Remarkably, no loss in voltage outputs was observed for the (p-TEA)(p-TEAH)PF6 devices even after exposure to 99% relative humidity, showcasing their utility under extremely humid conditions.
Keywords: 3D printing; cocrystals; energy harvesting; ferroelectricity; Piezoelectricity

Highly moisture-stable ferroelectric ammonium phosphate salt showing piezoelectric energy harvesting and rotation sensing applications - Kushwaha, Vikash; Prajesh, Neetu; Gopal, Animesh; Sahoo, Supriya; Deswal, Swati; Kirana, Antonysylvester; Shanmuganathan, Kadhiravan; Zareba, Jan K.; Boomishankar, Ramamoorthy (Journal of Materials Chemistry A, 2025)
Ferroelectric phosphate-based materials are known for their biocompatibility, dipole switching, and high thermal stability. In this context, we report a novel organic ferroelectric material, diisopropylammonium bis(4-nitrophenyl) phosphate (DIPABNPP), crystallizing in the monoclinic C2 space group. DIPABNPP exhibits a high second harmonic generation (SHG) efficiency 2.5 times higher than that of potassium dihydrogen phosphate (KDP). The ferroelectric nature of DIPABNPP was confirmed by the observation of a rectangular P-E hysteresis loop, which gave a saturated polarization value of 6.82 mu C cm-2. The ferroelectric polar domains of DIPABNPP, along with the bias-dependent amplitude butterfly and phase hysteresis loops, were visualized by piezoresponse force microscopy (PFM). Furthermore, the polydimethyl siloxane (PDMS) composites of DIPABNPP enabled the fabrication of humidity-resistant piezoelectric nanogenerators (PENGs) with energy harvesting and mechanical-electrical sensing capabilities. The top-performing 10 wt% DIPABNPP-PDMS device achieved a peak output voltage of 9.5 V and a charge storage efficiency of 81.8%, successfully powering 53 LEDs. Additionally, its rapid response time of 18.5 ms enables precise rotation sensing capabilities, suggesting potential applications in motion monitoring, such as revolution per minute (RPM) counting. We also present a unique and refined method for obtaining the output work efficiency (OWE) parameter, which quantifies the ratio of harvested electrical energy to the maximum elastic energy stored in the composite device, taking into consideration several key parameters during the PENG measurements. For the 10 wt% DIPABNPP-PDMS composite, an OWE of 13.1% was achieved, highlighting both its current performance and potential for optimization. This metric provides a standardized approach for evaluating PENGs, addressing a critical gap in assessing mechanical-to-electrical energy conversion efficiency.